(untitled) (Bangladesh Journal of Agricultural Research, 2014)
A field experiment was conducted at the Regional Wheat Research Centre (RWRC) of the Bangladesh Agricultural Research Institute, Gazipur, Bangladesh for 2 consecutive years during 2006-07 and 2007-08 with the objective to find out the optimum nutrient management practice on total dry matter production (above ground part) of each component crop of potatomungbean- t. aman rice cropping pattern. Twelve nutrient management treatments were tested in RCBD with 3 replications. Treatments were, T1=HYG (0-198-44-194-24-6-1.2), T2=MYG (0-140-34-138-18-4.5-0.9), T3=IPNS (10000-168-38-170-18-6-1.2), T4=STB (0-171-40-164-22-5-1), T5=FP (0-97-16- 91-0-0-0), T6=CON (0-0-0-0-0-0-0), T7=HYG+CRI, T8=MYG+CRI, T9=IPNS+CRI, T10=STB+CRI, T11=FP+CRI, T12=CON+CRI kg/ha CDNPKSZnB, for potato; T1=HYG (0-24-40-48-24-3-1.2), T2=MYG (0-20-36- 40-20-2-1), T3=IPNS (5000-9-37-36-21-3-1.2), T4=STB (0-20-36-40-22-2-1), T5=FP (0-6-5-4-0-0-0), T6=CON (0-0-0-0-0-0-0), T7=HYG+CRI , T8=MYG+CRI, T9=IPNS+CRI, T10=STB+CRI, T11=FP+CRI, T12=CON+CRI kg/ha CDNPKSZnB for mungbean and T1=HYG (0-80-16-44-12-2-0), T2=MYG (0-56-12-32-8-1.5-0), T3=IPNS (5000-65-13-32-9-2-0), T4=STB (0- 68-15-37-11-2-0), T5=FP (0-39-37-12-0-0-0), T6=CON(0-0-0-0-0-0- 0),T7=HYG+CRI, T8=MYG+CRI, T9=IPNS+CRI, T10=STB+CRI,T11=FP+CRI, T12=CON+CRI kg/ha CDNPKSZnB for t. aman rice. HYG treatment without or with crop residues incorporation produced the highest TDM in potato, mungbean and t. aman rice followed by IPNS and STB along with or without CRI. The lowest TDM was recorded in control plot without CRI. The increasing trend of TDM was observed in the crop residues incorporation plots than nonincorporation plots. It was observed that there were significant and positive linear relationship between TDM and yield of potao, mungbean, and t. aman rice at 60 DAP, 60 DAS, and 90 DAT, respectively, in both the years. DOI: http://dx.doi.org/10.3329/bjar.v39i2.20416 Bangladesh J. Agril. Res. 39(2): 211-225, June 2014